(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This study is an investigation on effective risk management with respect to organizations in Nigeria. The objective of the paper is to examine factors militating against effective risk management in organizations. The paper adopted content analysis of library materials, journal publications, internet materials and other documented materials relevant to the subject matter. It was concluded that effective risk management is a proactive approach towards mitigating the impact of threats, maximizing opportunities and optimizing the achievement of objectives. It was recommended that managers of organizations in Nigeria should imbibe and articulate good corporate risk attitude, strong risk culture and clearer risk appetite.